Increasing Productivity Growth in Middle Income Countries - Abdychev, Aidar (IMF Working Papers; Working Paper ;, 2015)
Many small middle-income countries (SMICs) in sub-Saharan Africa (SSA) have experienced a moderation in growth in recent years. Although factor accumulation, most notably capital deepening, was crucial to the success of many SMICs historically, this growth model appears to have run its course. The analysis in this paper suggests that the decline in the contribution of total factor productivity (TFP) to growth is largely responsible for the slowdown in trend growth in many SMICs, which highlights the need for policy actions to reinvigorate productivity growth. This paper explores the question of what kind of structural policies could boost productivity growth in SMICs and the political economy factors that may be contributing to the slow implementation of these critical reforms in these countries. The findings suggest that although macroeconomic stability and trade openness are necessary for productivity growth, they are not sufficient. SMICs need to improve the quality of their public spending, most notably in education to minimize the skill mismatch in the labor market, reduce the regulatory burden on firms, improve access to finance by small and medium-sized enterprises and create the enabling environment to facilitate structural transformation in these economies.